Tingkat Penerimaan Konsumen Terhadap Kaldu Bubuk Penyedap Rasa Berbahan Baku Udang Rebon (Acetes Erythraeus), Limbah Ikan Gabus (Channa Striata), Dan Limbah Udang Windu (Penaeus Monodon) - Ikromatun Nafsiyah; Muhammad Subhan Hamka; Triayu Rahmadiah; Muhammad Sumsanto (Pusat riset dan Inovasi Nasional, 2023)
Broth is a flavoring product which is generally produced from the process of cooking high-protein ingredients such as meat with water, with or without other additions. The flavoring broth that is favored generally made from chicken and beef, although fish and shrimp and even their waste can also be used to make natural flavoring broth. This research aims to determine the level of consumer preference of flavoring powder broth made from 3 ingredients/samples, namely snakehead fish waste, tiger prawn waste and rebon shrimp. This research was carried out by making powdered broth and hedonic test to determine the level of preference from consumers. This test used 25 semi-trained panelists with color, aroma, texture and taste parameters. The test results showed that flavoring powder broth made from snakehead fish waste was preferred by consumers in terms of texture, broth made from tiger prawn waste was highly preferred in terms of taste parameters, and samples made from rebon shrimp as raw materials were preferred in terms of color and aroma parameters